Forgotten, silent, and overruled: Hearing the voice of the nursing home patient. (November 2018) - Williams, Andrea; Cadick, Amber
As the population ages, more Americans are moving into nursing homes/long-term care facilities. Per Accreditation Council for Graduate Medical Education 2017 guidelines, family medicine residents are required to gain experience and competence working in long-term care facilities; however, this unique environment poses several challenges for residents to hear the wishes of their patients over the demands of the patient's medical care team and family members. Also, many patients in long-term care facilities have sensory impairments (e.g., poor eyesight, deafness) and/or cognitive deficits (e.g., dementia). One solution for hearing the patient's voice over the demands of medical professionals and family members is to train physicians on how to overcome communication barriers with their patients. This article will discuss solution-focused approaches to reducing the barriers of sensory and cognitive impairments through the use of adaptive communication behaviors and adaptive equipment. Ways to improve communication between physicians, nursing-home staff, and patients' family in order to improve the care patients receive in long-term care facilities will also be addressed. These recommendations are designed to assist with reducing physician frustration, increasing each patient's input in medical decision-making, and improving communication across the patient care team.